2016
DOI: 10.1371/journal.pone.0148184
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathogenicity of Two Saffold Virus Type 3 Isolates in Mouse Models

Abstract: ObjectiveSaffold virus (SAFV), a picornavirus, is occasionally detected in children with acute flaccid paralysis, meningitis, and cerebellitis; however, the neuropathogenicity of SAFV remains undetermined.MethodsThe virulence of two clinical isolates of SAFV type 3 (SAFV-3) obtained from a patient with aseptic meningitis (AM strain) and acute upper respiratory inflammation (UR strain) was analyzed in neonatal and young mice utilizing virological, pathological, and immunological methods.ResultsThe polyproteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 67 publications
4
13
0
Order By: Relevance
“…In addition SAFV can infect the heart and the CNS, as expected for a member of the genus Cardiovirus. These observations are congruent with those of Kotani et al (2016), which were published while this paper was in revision. These authors report the neuropathogenicity in mice, of two SAFV-3 clinical isolates.…”
supporting
confidence: 92%
“…In addition SAFV can infect the heart and the CNS, as expected for a member of the genus Cardiovirus. These observations are congruent with those of Kotani et al (2016), which were published while this paper was in revision. These authors report the neuropathogenicity in mice, of two SAFV-3 clinical isolates.…”
supporting
confidence: 92%
“…1 & Additional file 1: Figure S1), indicating that the virus infects both neuronal and glial cells, but neither exclusively. Our results agree with Sorgeloos et al [16] who showed infection of both neuronal and glial cells, but not with Kotani et al [17] who showed infection of glial cells, but not neuronal cells, in both early adult (6 week-old) and neonatal brains of ddY and BALB/c mice. However it should be noted that Sorgeloos et al [16] showed a preference to glial cells over neuronal cells.…”
Section: Resultssupporting
confidence: 82%
“…They further showed demyelination in the spinal cord of infected neonatal ddY mice spine in one of their strains, but not in adult mice. It should be noted that while Kotani et al showed demyelination, they attributed it to a TMEV infection rather than an effect of SAFV. Both our laboratory and Sorgeloos et al have also shown that it is highly unlikely that SAFV causes demyelination, and similarly in humans, Galama et al suggested that an association between SAFV and MS is highly improbable.…”
Section: Animal Models Of Safv Infectionmentioning
confidence: 97%
“…This was later supported by Sorgeloos et al when they demonstrated that infection of interferon receptor deficient (IFNAR‐KO) 129/sv mice permitted infection of the brain, spinal cord, heart, pancreas, and spleen. At the same time, Kotani et al showed that ic inoculation of SAFV causes non‐fatal infection of neonatal and 6‐week‐old ddY and BALB/c mice. They further showed demyelination in the spinal cord of infected neonatal ddY mice spine in one of their strains, but not in adult mice.…”
Section: Animal Models Of Safv Infectionmentioning
confidence: 99%
See 1 more Smart Citation